2013
DOI: 10.1158/1535-7163.mct-12-0885
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib Prolongs Survival Compared with Gefitinib in an Epidermal Growth Factor Receptor-Driven Lung Cancer Model

Abstract: An irreversible ErbB family blocker is expected to inhibit tumors with activating epidermal growth factor receptor (EGFR) mutations more strongly than reversible EGFR tyrosine kinase inhibitors and to overcome acquired resistance to the T790M secondary mutation. Eleven-week-old transgenic mice with Egfr exon 19 deletion mutation were treated with afatinib, gefitinib, or vehicle for 4 weeks. All mice were sacrificed at 15 weeks of age, and the number of superficial left lung tumors with a long axis exceeding 1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…We found that IC50 values were 0.28 nM for PC-9, 350.0 nM for PC-9-GR, 38.4nM for H1975 and 2.3μM for H460 cells, respectively. These results suggest that NSCLC cells with T790M mutant EGFR are relatively sensitive to afatinib than cells carrying wild-type EGFR, which is consistent with the reports from previous study [16]. Of note, we found that IC50 value of PC-9-GR cells were significantly higher than that of parental PC-9 cells, indicating that development of acquired resistance to gefitinib, or to other first-generation of TKIs, may also cause reduced sensitivity to second-generation of TKIs in NSCLC cells that were initially sensitive to these agents (Figure 2).…”
Section: Resultssupporting
confidence: 93%
“…We found that IC50 values were 0.28 nM for PC-9, 350.0 nM for PC-9-GR, 38.4nM for H1975 and 2.3μM for H460 cells, respectively. These results suggest that NSCLC cells with T790M mutant EGFR are relatively sensitive to afatinib than cells carrying wild-type EGFR, which is consistent with the reports from previous study [16]. Of note, we found that IC50 value of PC-9-GR cells were significantly higher than that of parental PC-9 cells, indicating that development of acquired resistance to gefitinib, or to other first-generation of TKIs, may also cause reduced sensitivity to second-generation of TKIs in NSCLC cells that were initially sensitive to these agents (Figure 2).…”
Section: Resultssupporting
confidence: 93%
“…Viable cells were measured using the modified 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetra-zolium bromide (MTT) assay (21,22).…”
Section: Drug Sensitivity Assaysmentioning
confidence: 99%
“…2) (Zhang et al 2006). Inhibition of autophosphorylation by afatinib has been shown for EGFR (Ioannou et al 2013; Kim et al 2012b; Ninomiya et al 2013; Solca et al 2012; Takezawa et al 2012; Tanaka et al 2012), HER2 (Canonici et al 2013; Ninomiya et al 2013; Solca et al 2012; Tabara et al 2012; Takezawa et al 2012; Tanaka et al 2012), ErbB4 (Solca et al 2012) and transphosphorylation of ErbB3 (Ioannou et al 2013; Kim et al 2012b; Tabara et al 2012; Takezawa et al 2012; Tanaka et al 2012) in a wide variety of cell lines representing lung (Kim et al 2012b; Lee et al 2013; Ninomiya et al 2013; Solca et al 2012; Tabara et al 2012; Takezawa et al 2012), breast (Solca et al 2012), gastric (Tanaka et al 2012), colorectal (Khelwatty SA, Essapen S, Seddon A, Modjtahedi H, in preparation) and pancreatic cancer (Ioannou et al 2013). Similar to the kinase inhibition studies, afatinib’s potency for inhibition of autophosphorylation was in the low nanomolar range.…”
Section: Effects At the Cellular Levelmentioning
confidence: 99%